Tibet : an unfinished story - Halper, Lezlee Brown; Halper, Stefan A. (Oxford University Press, 2014)
"The mythologising of Tibet in the West and the Himalyan state's subsequent abandonment to China are recounted in this briskly-paced and revealing new history"--